2003
DOI: 10.1017/s0950268803008793
|View full text |Cite
|
Sign up to set email alerts
|

The infection rate of Daphnia magna by Pasteuria ramosa conforms with the mass-action principle

Abstract: In simple epidemiological models that describe the interaction between hosts with their parasites, the infection process is commonly assumed to be governed by the law of mass action, i.e. it is assumed that the infection rate depends linearly on the densities of the host and the parasite. The mass-action assumption, however, can be problematic if certain aspects of the host-parasite interaction are very pronounced, such as spatial compartmentalization, host immunity which may protect from infection with low do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(134 citation statements)
references
References 25 publications
3
122
3
Order By: Relevance
“…The estimated infection probability is lower than the one we found previously (Regoes et al 2003), a difference we elaborate on below. We can calculate the ID 50 (i.e.…”
Section: Results (A) Infection Experimentscontrasting
confidence: 71%
See 1 more Smart Citation
“…The estimated infection probability is lower than the one we found previously (Regoes et al 2003), a difference we elaborate on below. We can calculate the ID 50 (i.e.…”
Section: Results (A) Infection Experimentscontrasting
confidence: 71%
“…Although the purity of the parasite isolates is an important issue for a binary interpretation of the infection process, we would like to emphasize that it does not play a role in deviance from the mass-action model that we observed here. In a previous study, we showed that the observed deviations from the mass-action infection model cannot be explained by parasite heterogeneity or stochastic effects (Regoes et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Juveniles were exposed to spores by placing them singly in 100-ml beakers filled with 20 ml of medium and adding spore suspensions containing 200 000 spores of P. ramosa clone C1. This dose is known to cause 100% infections without lethal effect in susceptible hosts (Regoes et al, 2003). Individual D. magna remained in 20 ml of medium for 4 days, at which point the beakers were filled up.…”
Section: Tests For Susceptibilitymentioning
confidence: 99%
“…Spore doses were created by homogenizing several infected Daphnia and counting the resulting spore concentration with a haemocytometer under a light microscope. We chose to infect Daphnia with a spore dose (16 000 spores) that was previously found to result in intermediate (60-80%) infection rates (Regoes et al 2003). Daphnia were exposed to spores for six days, after which they were transferred to fresh pathogen-free water.…”
Section: Infection Rate Experimentsmentioning
confidence: 99%
“…Under conditions of high food quantity and quality, previous research has shown Pasteuria to be highly effective at infecting Daphnia (Regoes et al 2003). Pasteuria infections in Daphnia are generally nonreversible and greatly reduce daphnid fitness (Ebert 2005).…”
Section: Introductionmentioning
confidence: 99%